Oral and Maxillofacial Surgery for the Clinician 2021
DOI: 10.1007/978-981-15-1346-6_65
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular Joint Ankylosis

Abstract: The purpose of this chapter is to inculcate a newer, deeper understanding of TMJ Ankylosis– both from the pathological as well as the clinical view point. Newer classifications may now determine surgical procedures. Interpositional materials may not be just soft tissues interposed between the cut ends, but also hard tissues forming the new Ramus Condyle Unit (RCU). Facial deformity may be recognized to be as important as inability to open the mouth; more so, if accompanied by Obstructive sleep apnea (OSA). Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…In our case, the external appearance suggested right-sided mandibular hypoplasia; however, the associated left-sided TMJ ankylosis caused the jaw to be pulled towards the left side, creating the illusion of hypoplasia on the right side. This observation underscores the importance of comprehensive clinical assessment and radiographic evaluation in determining the true nature of mandibular abnormalities [ 17 ].…”
Section: Discussionmentioning
confidence: 97%
“…In our case, the external appearance suggested right-sided mandibular hypoplasia; however, the associated left-sided TMJ ankylosis caused the jaw to be pulled towards the left side, creating the illusion of hypoplasia on the right side. This observation underscores the importance of comprehensive clinical assessment and radiographic evaluation in determining the true nature of mandibular abnormalities [ 17 ].…”
Section: Discussionmentioning
confidence: 97%
“…After that, the fragment is positioned to address the anteroposterior and midline deficit. Patients with a normal ramus dimension, functional occlusion, insufficient/ standard posterior airway space, or unilateral ankylosis may benefit from orthomorphic osteotomies 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a lack of comprehensive studies on the prevalence of TMJA at various geographic levels, Gupta et al found a prevalence of 0.46 per 1000 among three to 15-year-olds in rural and urban areas of Lucknow, India, in 2012 [ 1 ]. TMJA can manifest at any age, resulting in restricted mouth opening and facial asymmetry [ 2 ]. The prognosis is seen to be negatively correlated with the number of years with TMJA.…”
Section: Introductionmentioning
confidence: 99%